Time to take CT screening to the next level? - Kauczor, Hans-Ulrich; Heußel, Claus Peter; Stackelberg, Oyunbileg von (The European respiratory journal, 2017)
Tweetable abstract ERSpublications click to tweetTransforming lung cancer screening into a comprehensive programme to detect and treat smoking-related disease early http://ow.ly/b8L5309hUri